Implementation of Statistical Process Control and Failure Mode and Effect Analysis for Quality Control of Steel Plate Products - Djunaidi, Much; Priyadi, Putri Ana Wahyu; Fitriadi, Ratnanto; Nursanti, Ida (Jurnal Ilmiah Teknik Industri, 2025)
The rapid growth of the manufacturing industry has heightened the demand for high-quality products, particularly steel plates, which are extensively utilized across various construction and engineering sectors. To ensure consistent product quality, a systematic quality control approach is essential. This study was conducted at PT XYZ with the objective of implementing Statistical Process Control (SPC) and Failure Mode and Effect Analysis (FMEA) to monitor and analyze potential failures throughout the production process. The research focused on evaluating production data and the number of defective products over a one-year period. SPC was employed to assess the stability of the production process, while FMEA was utilized to identify the most critical failure modes based on their Risk Priority Number (RPN). The analysis revealed that the total percentage of defective products reached 9.1%, significantly exceeding the company's tolerance threshold. Among the identified defect types, Under Length and Wavy Edge were the most dominant, each contributing 4.5% to the total defects. These findings highlight the urgent need for corrective actions to reduce the defect rate and improve overall product quality.